Jail and prisons in Córdoba del Tucumán - Aspell, Marcela (2008)
The present investigation was carried out by collating the documentary funds of the Historical Archive and the Archive of the Archbishopric of Córdoba to study the formation and development of the capitular jail, the jail and the application of prison sentences in Córdoba del Tucumán. This is an Indian city founded by Spaniards in 1573, a crossroads and communications hub for pilgrims who traveled the routes to Buenos Aires, Asunción, Santiago or Lima, far from the theater of war but a permanent border with the Indian; likewise, it was the head of the bishopric and the seat of the university that in 1791 would incorporate the regular studies of Law, with the Institute Chair, a fact that meant the creation of the Faculty of Jurisprudence. The presence of regular law studies contributed to spreading knowledge and consolidating the practice of law to replace a justice of lay judges, whose operation was determined to control a distant higher court.